Alkyl bisimidazolium-mediated crosslinked comb-shaped polymers as highly conductive and stable anion exchange membranes. Issue 20 (8th February 2016) - Rao, Anil H. N.; Nam, SangYong; Kim, Tae-Hyun
Abstract : Crosslinked poly(arylene ether sulfone)s (PES) with pendant alkyl bisimidazolium units, which act as both crosslinkage sites and hydroxide conductors, were developed as anion exchange membranes (AEMs). Abstract : Crosslinked poly(arylene ether sulfone)s (PES) with pendant alkyl bisimidazolium units, which act as both crosslinkage sites and hydroxide conductors, were developed as anion exchange membranes (AEMs). These bisimidazolium-mediated crosslinked membranes (BI-cPESs) display a high hydroxide conductivity exceeding 0.012 S cm −1 at 20 °C and 0.061 S cm −1 at 80 °C, together with good chemical, thermal, mechanical, oxidative and dimensional stabilities. The BI-cPES membrane, which includes a long alkyl chain (C10, BI-cPES-10), form self-aggregated structures due to the long pendant hydrophobic side chain that forms a comb shape. The benefit of this crosslinked comb-shaped system is its high conductivity of 0.027 S cm −1 at 20 °C, even at an IEC as low as 1.13 meq. g −1 and a low water uptake of 8.70%.